Leadership in Organizations and the PR Department Work Quality - Edit Terek Stojanović; Mila Kavalić; Sanja Kovačić; Milan Nikolić; Marko Vlahović; Srđana Taboroši (Management)
Research Question: This paper examines the influence of individual leadership dimensions on individual public relations dimensions. The transformational and transactional leadership dimensions, as well as the ethical leadership behavioural dimensions were considered as the independent variables in the study. As the dependent variables, the dimensions of the PR department work quality were considered: Ethical and Responsible Action, Proactive and Quality Performance, Strategic and Effective Action, Media Relations and Internal Public Relations. The paper also analyzes the moderating effects of leaders’ gender and leaders’ age on the observed relationships. Motivation: Previous research linking leadership and public relations can generally be divided into two groups. One group of such studies addresses the impact of leadership on public relations (Topic, 2021; Meng & Neill, 2021). The other research group relates to examining and defining the characteristics of leadership in public relations (Martinelli & Erzikova, 2017; Killingsworth & Flynn, 2016; Hamrin, 2016). However, the impression gained is that there is a lack of research which focuses on measuring the direct impacts of individual leadership dimensions on individual public relations dimensions, especially at the organizational level. This is even more emphasized when examining the influence of the dimensions of transformational leadership and ethical leadership behaviour. Idea: The idea is leadership in organizations has an impact on a number of individual and organizational performance indicators, including public relations and effectiveness in public relations. The paper also analyzes the moderating effects of leaders’ gender and leaders’ age on the observed relationships. Data: The research was carried out in Serbian companies. The respondents included PR managers, PR practitioners and marketing professionals. A total of 236 questionnaires were collected from 78 companies. Tools: The descriptive statistics for all of the observed dimensions. The correlation coefficients between the leadership dimensions and the PR department work quality dimensions. Regression analysis the leadership dimensions on the PR department work quality dimensions. Leaders’ gender and age as a moderator of the observed relationships. Findings: Transformational leadership has a greater impact than transactional. The influence of the Contingent Punishment Behaviour dimension can be negative as can that of Intellectual Stimulation. Female and older leaders have a greater influence on the PR department work quality dimensions. The impression is that female and older leaders have a stricter, more decisive and emotional management style, so the results of the PR department are more aligned with such requirements. Contribution: Such research would create a theoretical basis for the practical action of leaders in the promotion of public relations, especially in terms of individual public relations dimensions.